Identification of inorganic waste at mangrove ecosystem, Gampong Jawa, Banda Aceh. Issue 1 (February 2021) - Agustina, S; Khairullah, K; Rusydi, I; Purnawan, S; Karina, S; Zamzami, Z
Abstract: The plastic pollution entering the ocean has been global concern. However, the research about the mangrove ecosystem poses the plastic waste in Aceh Province is limited. This study aims to investigate the inorganic waste based on type and its abundance in mangrove area at Gampong Jawa, Banda Aceh. Transect was installed along 6m x 100m at three stations. The total waste collected was 134 items with the most abundance was plastic (126 items). The most common type found at the three stations was plastic bags. Rubber and glass were also observed trapped in Gampong Jawa's mangrove area. The high level of debris abundance at station 1 was suspected because station 1 has the highest mangrove density so that allows the debris trapped at the mangrove roots. Stations 2 and 3 have less debris abundance because the low density of mangroves.